The changeling eaudiobook A novel. - LaValle, Victor (Random House Audio, 2017)
“Mesmerizing . . . a dark fairy tale of New York, full of magic and loss, myth and mystery, love and madness.”—Marlon James, author of the Dark Star trilogy NOW AN APPLE TV+ SERIES STARRING LAKEITH STANFIELD • ONE OF TIME ’S 100 BEST FANTASY BOOKS OF ALL TIME Winner of an American Book Award, a Locus Award for Best Horror Novel, a British Fantasy Award for Best Horror Novel, a World Fantasy Award for Best Novel • Nominated for a Shirley Jackson Award, an International Dublin Literary Award, a Mythopoeic Award for Literature When Apollo Kagwa’s father disappeared, he left his son a box of books and strange recurring dreams. Now Apollo is a father himself—and as he and his wife, Emma, settle into their new lives as parents, exhaustion and anxiety start to take their toll. Apollo’s old dreams return and Emma begins acting odd. At first Emma seems to be exhibiting signs of postpartum depression. But before Apollo can do anything to help, Emma commits a horrific act and vanishes. Thus begins Apollo’s quest to find a wife and child who are nothing like he’d imagined. His odyssey takes him to a forgotten island, a graveyard full of secrets, a forest where immigrant legends still live, and finally back to a place he thought he had lost forever. NAMED ONE OF PASTE ’S BEST HORROR BOOKS OF THE DECADE • NAMED ONE OF THE BEST BOOKS OF THE YEAR BY The New York Times • USA Today • The New York Public Library • NPR • BuzzFeed • Kirkus Reviews • Book Riot “The thriller you won’t be able to put down.” —O: The Oprah Magazine “Intense, riveting . . . The story is a long, slow burn with a lingering sizzle.” — Los Angeles Review of Books “A modern-day tale of terror rooted in ancient myth and folklore, brimming with magical revelation and emotional truth.” — San Francisco Chronicle